CAR-T therapy toxicities: the importance of macrophages in their development and possible targets for their management - Joseph Norton; Patrick Stiff (Discover Oncology)
Abstract CAR-T cell therapies have risen to prominence over the last decade, and their indications are increasing with several products approved as early as second line in Large B Cell non-Hodgkin Lymphomas. Their major toxicities are the cytokine release syndrome (CRS) and the Immune-effector Cell Associated Neurotoxicity Syndrome (ICANS). These entities involve a hyperinflammatory cascade which is amplified through the mononuclear phagocytic system (MPS). Herein, we review the immune mediated adverse events related to CAR therapy, including their pathophysiologies, and current therapies. In particular, we discuss the emerging role of the MPS in both the toxicity and efficacy of CAR-T therapy, and possible avenues for the modulation of the MPS to optimize efficacy while minimizing toxicity.